The autophagy-related genes BbATG1 and BbATG8 have different functions in differentiation, stress resistance and virulence of mycopathogen Beauveria bassiana - Ying, Sheng-Hua (Sci Rep, 2016)
Autophagy-related proteins play significantly different roles in eukaryotes. In the entomopathogenic fungus Beauveria bassiana, autophagy is associated with fungal growth and development. BbATG1 (a serine/threonine protein kinase) and BbATG8 (a ubiquitin-like protein) have similar roles in autophagy, but different roles in other processes. Disruption mutants of BbATG1 and BbATG8 had impaired conidial germination under starvation stress. The mutant ΔBbATG8 exhibited enhanced sensitivity to oxidative stress, while a ΔBbATG1 mutant did not. BbATG1 and BbATG8 showed different roles in spore differentiation. The blastospore yield was reduced by 70% and 92% in ΔBbATG1 and ΔBbATG8 mutants, respectively, and the double mutant had a reduction of 95%. Conidial yield was reduced by approximately 90% and 50% in ΔBbATG1 and ΔBbATG8 mutants, respectively. A double mutant had a reduction similar to ΔBbATG1. Additionally, both BbATG1 and BbATG8 affected the levels of conidial protein BbCP15p required for conidiation. The virulence of each autophagy-deficient mutant was considerably weakened as indicated in topical and intrahemocoel injection assays, and showed a greater reduction in topical infection. However, BbATG1 and BbATG8 had different effects on fungal virulence. Our data indicate that these autophagy-related proteins have different functions in fungal stress response, asexual development and virulence.